Chemical constituents of the stems of Neolitsea kedahensis Gamble. (August 2018) - Jani, Nor Akmalazura; Sirat, Hasnah Mohd; Ahmad, Farediah; Abed, Salam Ahmed; Aminudin, Nurul Iman
Graphical abstract: Highlights: Two new β -carboline alkaloids (1–2) were isolated from Neolitsea kedahensis . One new sesquiterpene dilactone (3) was obtained from Neolitsea kedahensis . The relative configuration of (3) was determined by X-ray crystallography. Abstract: Two new β -carboline alkaloids, daibucarbolines D (1 ) and E (2 ) and one new sesquiterpene dilactone, pseudovillosine (3 ), together with five known compounds, taraxerone, taraxerol, pseudoneoliacine, daibucarboline A and linderaggrine A were isolated from the stems of Neolitsea kedahensis (Lauraceae). The structures were confirmed through extensive spectroscopic analysis, while the relative configuration of compound (3 ) was determined by a single crystal X-ray diffraction.